Unraveling the influence of lanthanide ions on intra- and inter-molecular electronic processes in Fe 10 Ln 10 nano-toruses - Baniodeh, A; Liang, Y; Anson, C; Magnani, N; Powell, A; Unterreiner, A; Seyfferle, S; Slota, M; Dressel, M; Bogani, L; Goß, K (Wiley, 2014)
We investigated the electronic properties of the molecular magnetic nanoto-ruses [Fe III10LnIII10(Me-tea)10(Me-teaH)10(NO3)10], examining the dependence on the lanthanide (Ln) of both the intra and intermolecular electronic channels. Using femtosecond absorption spectroscopy we show that the intramolecular electronic channels follow a three-step process, which involves vibrational cooling and crossing to shallow states, followed by recombination. A comparison with the energy gaps showed a relationship between trap efficiency and gaps, indicating that lanthanide ions create trap states to form excitons after photo-excitation. Using high-resistance transport measurements and scaling techniques, we investigated the intermolecular transport, demonstrating the dominant role of surface-limited transport channels and the presence of different types of charge traps. The intermolecular transport properties can be rationalized in terms of a hopping model, and a connection is provided to the far-IR spectroscopic properties. Comparison between intra and intermolecular processes highlights the role of the excited electronic states and the recombination processes, showing the influence of Kramers parity on the overall mobility.